Prediction of risk and multilevel program of prevention the children invalidity (Texas Journal of Multidisciplinary Studies, 2023)
Children's disability is a major problem today. Hundreds of thousands of disabled children need attention and support of society, social, medical and other assistance. The relevance of this issue indicates the quantitative growth of disability in childhood and adverse trends in its structure